Peroxisome proliferator-activated receptor-δ-mediated upregulation of catalase helps to reduce ultraviolet B-induced cellular injury in dermal fibroblasts. Issue 3 (September 2021) - Hur, Jinwoo; Kang, Eun Sil; Hwang, Jung Seok; Lee, Won Jin; Won, Jun Pil; Lee, Hyuk Gyoon; Kim, Eunsu; Seo, Han Geuk
Highlights: PPAR-δ induces expression of catalase via PPRE in human dermal fibroblasts (HDFs). PPAR-δ also reverses the reduction in activity and expression of catalase induced by UVB irradiation. This PPAR-δ-mediated upregulation of catalase protects the HDFs from cellular damage triggered by UVB irradiation. Catalase is a target of PPAR-δ, and elicits the cellular response of PPAR-δ against oxidative stress. Abstract: Background: Previous studies suggested that the nuclear receptor peroxisome proliferator-activated receptor (PPAR)-δ plays an essential role in cellular responses against oxidative stress. Objective: To investigate how PPAR-δ elicits cellular responses against oxidative stress in primary human dermal fibroblasts (HDFs) exposed to ultraviolet B (UVB). Methods: The present study was undertaken in HDFs by performing real-time polymerase chain reaction, gene silencing, cytotoxicity and reporter gene assay, analyses for catalase and reactive oxygen species, and immunoblot analyses. Results: The PPAR-δ activator GW501516 upregulated expression of catalase and this upregulation was attenuated by PPAR-δ-targeting siRNA. GW501516-activated PPAR-δ induced catalase promoter activity through a direct repeat 1 response element. Mutation of this response element completely abrogated transcriptional activation, indicating that this site is a novel type of PPAR-δ response element. In addition, GW501516-activated PPAR-δ counteracted the reductions in activity and expression of catalase induced by UVB irradiation. These recovery effects were significantly attenuated in the presence of PPAR-δ-targeting siRNA or the specific PPAR-δ antagonist GSK0660. GW501516-activated PPAR-δ also protected HDFs from cellular damage triggered by UVB irradiation, and this PPAR-δ-mediated reduction of cellular damage was reversed by the catalase inhibitor or catalase-targeting siRNA. These effects of catalase blockade were positively correlated with accumulation of reactive oxygen species in HDFs exposed to UVB. Furthermore, GW501516-activated PPAR-δ targeted peroxisomal hydrogen peroxide through catalase in UVB-irradiated HDFs. Conclusion: The gene encoding catalase is a target of PPAR-δ, and this novel catalase-mediated pathway plays a critical role in the cellular response elicited by PPAR-δ against oxidative stress.